2007
DOI: 10.1139/h07-116
|View full text |Cite
|
Sign up to set email alerts
|

The effects of whole-body vibration on upper- and lower-body EMG during static and dynamic contractions

Abstract: Whole-body vibration (WBV) training uses a vertically oscillating platform and reports suggest that this perturbation elicits reflexive muscle contractions that augment muscle activity and contribute to increased strength. No WBV study has measured both upper- and lower-body muscle activation. The purpose of this study was to determine the optimal WBV stimulus (frequency x amplitude) to increase electromyography (EMG) in upper- and lower-body muscles for three distinctive unloaded actions: isometric semi-squat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
173
2
16

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(203 citation statements)
references
References 36 publications
12
173
2
16
Order By: Relevance
“…Furthermore, in healthy subjects, greater EMG activity with high-frequency WBV training (40 and 45 Hz) has been reported when compared with lower frequencies (25 and 30 Hz). 8 In our study, the lack of differences in the EMG activity between frequencies could be due to the reduced EMG response of SCI patients in respect to healthy subjects, 21 as well as to the marked difference in the EMG patterns among SCI subjects; 21 therefore, this lack of statistical significance could be due to a type II error.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Furthermore, in healthy subjects, greater EMG activity with high-frequency WBV training (40 and 45 Hz) has been reported when compared with lower frequencies (25 and 30 Hz). 8 In our study, the lack of differences in the EMG activity between frequencies could be due to the reduced EMG response of SCI patients in respect to healthy subjects, 21 as well as to the marked difference in the EMG patterns among SCI subjects; 21 therefore, this lack of statistical significance could be due to a type II error.…”
Section: Discussionmentioning
confidence: 58%
“…6 Therefore, part of the rehabilitation of SCI patients should focus on the activation of muscular and vascular systems. 4 The application of whole-body vibration (WBV) with platforms has been shown to improve muscular 7,8 and vascular [9][10][11] functions. These effects are strongly dependent on the type of platform, protocols and vibration parameters (that is, frequency).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vib ra ti ons in the 30-100 Hz fre qu ency range we re re por ted to pro vi de mo re in cre a se in musc le elec trom yog rap hic (EMG) ac ti vity. 10,19,23 The fre qu ency of vib ra ti on was 46 Hz in the study.…”
Section: Ex Pe Rimen Tal Tests and Me A Su Re Mentsmentioning
confidence: 77%
“…[9][10][11][12][13] Pre vi o us stu di es have shown that vib ra ti on in cre a ses musc le elec tromyog ra hic (EMG) ac ti vity. [14][15][16][17][18][19][20][21][22] But, it has not be en re por ted whet her bo ne has an ef fect on the in crea se in musc le EMG ac ti vity ca u sed by vib ra ti on or not. The aim of this study was to de ter mi ne whether ra di us bo ne ex po sed to cyclic mec ha ni cal lo ading af fects musc le elec tri cal ac ti vity of m. fle xor car pi ra di a lis in he althy adult vo lun te ers.…”
mentioning
confidence: 99%